Transcriptomic and Widely Targeted Metabolomic Approach Identified Diverse Group of Bioactive Compounds, Antiradical Activities, and Their Associated Genes in Six Sugarcane Varieties - Muhammad Junaid Rao; Mingzheng Duan; Jihong Wang; Shijian Han; Li Ma; Xinyi Mo; Min Li; Lihua Hu; Lingqiang Wang (Antioxidants, 2022)
Sugarcane is cultivated mainly for its high sucrose content but it can also produce many metabolites with promising antioxidant potential. However, very few studies have been reported on the biosynthesis of metabolites in sugarcane to date. In this study, we have identified a wide range of amino acids and organic acids in the rind of six sugarcane varieties by the LC-MS/MS method. A total number of 72 amino acids and 55 organic acid compounds were characterized; among these, 100 were reported for the first time. Moreover, 13 amino acids and seven organic acids were abundantly distributed in all varieties tested and considered major amino acids and organic acids in sugarcane. The variety Taitang134 (F134) showed the highest content of total amino acids, whereas the varieties ROC16 and Yuetang93/159 (YT93/159) had maximum content of organic acids. The amino acids of the rind extract presented higher antioxidant capacity than the organic acids of the rind extract. In addition, the transcriptomic and metabolic integrated analysis highlighted some candidate genes associated with amino acid biosynthesis in sugarcane. We selected a transcription factor gene, MYB(t), and over-expressed it in Arabidopsis. The transgenic plants showed a higher accumulation of amino acids with higher antiradical activity compared with the wild-type Arabidopsis plants. Thus, we characterize a wide range of amino acids and organic acids and their antiradical activities in different sugarcane varieties and present candidate genes that can be potentially valuable for the genetic improvement of metabolites in sugarcane bagasse